PERAN GURU DALAM MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AKHLAK DI MADRASAH TSANAWIYAH AT-TAQWA 08 PEKAYON JAYA BEKASI SELATAN - Zamah Syary, Achmad; Supriyanto, Agus (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2016)
The problem of this article is how the role of teachers in improving student achievement lesson in aqidah-akhlaq at MTs At-Taqwa 08 Pekayon Jaya Bekasi Selatan? From the results of the study authors found that the role of teachers in improving student achievement in subjects aqidah-akhlaq already quite good, proven role of the teacher has to follow the procedures that are used in continuous learning process to prepare lesson plans, syllabi, and choose metode. Beside classroom educators as well act as mentors in improving student achievement in subjects aqidah-akhlaq with Duha prayer in congregation, which in this there are two aspects of aqidah-akhlaq, with debate method (mujaddalah) is by way of a good discussion conducted in a manner that is both gentle and affection. This method is very demanding role of teacher as a mediator and an organizer